Performance Analysis of Smart Speed Variation in Electric Vehicles Using the Combination of Fuzzy Logic Controller - Imo, F. U.; Aluhumile, Erukpe P.; Nwabueze, C. A. (Darul Yasin Al Sys, 2025)
Electric vehicles (EVs) have emerged as a response to the increasing environmental impact of combustion engines and the rising demand for fossil fuels, offering a sustainable alternative to meet the growing transportation needs that underpin economic development. Ensuring the safe operation of EVs on existing road infrastructure, particularly in environments with physical speed breakers, remains a critical concern. Speed bumps are commonly used to prevent collisions due to excessive speeding; however, they often compromise driving comfort and pose safety risks when encountered unexpectedly. This study proposes a smart speed control system for electric vehicles using a fuzzy logic controller, aimed at replacing traditional speed breakers. The system operates by deploying a transmitter at the entry point of a speed-regulated road segment, which sends speed limit data to approaching vehicles equipped with a corresponding receiver. Upon receiving the signal, the vehicle's speed is automatically adjusted to the designated limit. Once the vehicle exits the speed-restricted zone, a new signal allows it to resume normal speed. Developed using MATLAB/Simulink, the fuzzy logic-based control system not only enhances road safety and driving comfort but also contributes to energy efficiency in EVs. The successful implementation of this vehicle-to-infrastructure (V2I) communication model demonstrates the feasibility of intelligent speed regulation, suggesting its integration as a standard feature in future EVs. This approach provides traffic authorities with a proactive means of managing vehicle speed without direct driver intervention.